Analisis Semiotika Pesan Moral Pada Film How To Make Milions Before Grandma Dies - Siti Aisyah (PT. Pustaka Cendekia Publisher, 2024)
This study is entitled “Semiotic Analysis of Moral Messages in the Film How to Make Millions Before Grandma Dies”. The purpose of this study is to determine the moral message contained in the film How to Make Millions Before Grandma Dies using semiotic analysis through scenes containing moral messages in the film. The researcher used a qualitative method by recording and analyzing scenes containing moral messages in the film How to Make Millions Before Grandma Dies. Roland Barthes' semiotic approach was applied to identify and understand the meaning of denotation, connotation, and myth that appear in the visual elements, dialogue, and symbols in the film. The results of the study indicate that the moral message contained in the film How To Make Millions Before Grandma Dies includes three categories, namely, the relationship between humans and God, the relationship between humans and themselves, and the relationship between humans and other humans in the social environment including nature. Through a semiotic approach, this study successfully revealed that films not only function as entertainment media, but also as a medium for conveying moral messages. With in-depth analysis, this study is expected to contribute to the study of film and visual communication, as well as a reference for similar research in the future.